2020
DOI: 10.1039/d0ra05802e
|View full text |Cite
|
Sign up to set email alerts
|

Impact of benzannulation on ESIPT in 2-(2′-hydroxyphenyl)-oxazoles: a unified perspective in terms of excited-state aromaticity and intramolecular charge transfer

Abstract: Benzannulation of a typical fluorophore reveals the interplay between ESIPT, excited-state aromaticity and intramolecular charge transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 54 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…105,106,119 It is well known that the proton transfer abilities and emission properties of ESIPT-capable molecules can be tuned by substitution on the proton-donating and protonaccepting cores, as well as by the degree of π-conjugation. [120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136] As far as the degree of π-conjugation is concerned, extending the π-conjugated system on the protondonating part of the molecule can frustrate the ESIPT process, since the excited state is located predominantly on the ESIPT-incapable part of the molecule and involves the ESIPT site only to a small extent. 135,136 Instead, the extension of the π-conjugated system on the proton-accepting moiety could facilitate the ESIPT process due to better delocalization of a positive charge.…”
Section: Introductionmentioning
confidence: 99%
“…105,106,119 It is well known that the proton transfer abilities and emission properties of ESIPT-capable molecules can be tuned by substitution on the proton-donating and protonaccepting cores, as well as by the degree of π-conjugation. [120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136] As far as the degree of π-conjugation is concerned, extending the π-conjugated system on the protondonating part of the molecule can frustrate the ESIPT process, since the excited state is located predominantly on the ESIPT-incapable part of the molecule and involves the ESIPT site only to a small extent. 135,136 Instead, the extension of the π-conjugated system on the proton-accepting moiety could facilitate the ESIPT process due to better delocalization of a positive charge.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it appears that the driving force for the process is the relief of the antiaromaticity of ring A, which corroborates previous studies aimed at identifying general mechanistic principles for ESPT reactions. [28][29][30][31] Furthermore, owing to the observation in Fig. 2 that the antiaromaticity is relieved in a markedly smooth fashion along the reaction coordinate, it is clear that one would have arrived at an identical conclusion through calculations focusing strictly on the initial dienol and the final diketo species.…”
mentioning
confidence: 94%
“…[25][26][27] Specifically, when the proton donor/acceptor is a p-conjugated ring, ESA and ESAA help unravel the equilibrium between the species transformed by the proton transfer. Similarly, gains in ESA or losses in ESAA have been identified as the driving force for such reactions in many different systems, both when occurring independently [28][29][30][31] or coupled to other processes. 32,33 Yet, with few exceptions, 32 analyses undertaken to investigate the effect of aromaticity on these reactions have usually focused on the (anti)aromatic character of the reactants and products alone.…”
mentioning
confidence: 99%
“…Moreover, it has been more recently demonstrated that other relevant factors can also act together with hydrogen bonds in the ESIPT reaction, such as the pK a of the OH, the electron density shape along OH-N, and the symmetry of the aromatic orbitals. 47,48 In the present study, we investigated PQ-1 and PQ-2 in detail to theoretically examine their ESIPT mechanisms in relation to different hydrogen-bond lengths by using density functional theory (DFT) and time-dependent (TD-DFT) methods. The PQ-3 molecule associated with a seven-member-ring carbocycle between the phenol and quinolone was not studied in this work because of its totally different nonplanar effect.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been more recently demonstrated that other relevant factors can also act together with hydrogen bonds in the ESIPT reaction, such as the p K a of the OH, the electron density shape along OH–N, and the symmetry of the aromatic orbitals. 47,48 …”
Section: Introductionmentioning
confidence: 99%